Estudo de antenas para comunicação na faixa de subterahertz - Sousa, Jonas Rodrigo da Silva (2016)
The antennas in nano-metric scales are part of a line of research that has been gaining strength in recent years, being the target of numerous studies and publications in several universities in Brazil and around the world. Nano antennas are characterized as a promising new branch in the development of devices capable of being applied in different areas, in addition to communication. Occupying a prominent place in the new era of technologies, the nano antennas, here restricted only to dipole and microstrip, generate enormous expectations about this new revolution, not only between researchers, but also in a part of society. Currently, wireless communications require that radiator devices have wide bandwidth and miniaturization for mobile devices, so this dissertation discusses the potential application of antennas for communications in the frequency range in Terahertz. At these frequencies, there are numerous restrictions on the propagation of signals, so high performance antenna are necessary to allow communication with reduced losses. The purpose of this work is to study some configurations and types of antennas, such as microstrip antenna and dipole antenna, with application in the subterahertz frequency, which can be used, for example, in internal networks, medicine, photovoltaic power generation, spectroscopy, near-field microscopy and high quality images. Some configurations of antennas with various materials for communications in the frequency range will be presented to verify the feasibility of the use of nano dipole antennas and miniaturized microstrip antennas in this type of application. The methodology adopted suggests the comparison of the simulated results, through the software Ansoft HFSS ® and CST Microwave Studio ®, with the results of other published works